Use of Ameliorants to Increase Growth and Yield of Maize (Zea mays L.) in Peat Soils of West Kalimantan - Suswati, Denah; Sunarminto, Bambang Hendro; Shiddieq, Dja’far; Indradewa, Didik (JOURNAL OF TROPICAL SOILS, 2014)
Peatland in Indonesia has a potential for maize cultivation, but it has constraints that low of soil pH and of nutrient availability. Use of ameliorants from coastal sediment and salted fish waste was an alternative to improve peatlands productivity and maize yields. Objective of the study was to examine effects of coastal sediment and salted fish waste on growth and yield of maize at three kinds of soil of peatlands of Kubu Raya, West Kalimantan. This research was conductedÂ  inÂ  fieldÂ  usingÂ  Inter-area analysisÂ  design.Â  TheÂ  firstÂ  factorÂ  wasÂ  combinationÂ  ofÂ  each ameliorantsÂ  which consisted of 5 levels, namely: 1) treatment under farmer custom at the sites (control); 2) coastal sediment of 20 Mg ha-1 + 0.75 Mg of salted fish waste ha-1; 3) coastal sediment of 40 Mg ha-1 + 1.5 Mg of salted fish waste ha-1, 4) coastal sediment of 60 Mg ha-1 + 2.25 Mg of salted fish wasteÂ  ha-1. The second factor was soil types which consisted of three levels, namely: Typic Haplohemists, Typic Sulfisaprists and Typic Haplosaprists. Each treatment was repeated 5 times. The results showed that combination of 40 Mg ha-1 of coastal sediment and 1.5 Mg ha-1 of salted fish waste was the best combination for all soil type. It increased plant height (33% - 44%), shoot dry weight (74% - 75%), number of seeds per cob (31% -110%), weight of 100 seeds (58% -71%) and dry grain weight per plant (136 % -160 %) at each soil. The highest yield was found in soil of Typic Haplosaprists (219.54 g), followed by Typic Sulfisaprists (210.72 g) and Typic Haplohemists (208.82 g).Keywords: Coastal sediment, maize, peat soils, salted fish waste [How to Cite: Denah S, BH Sunarminto, D Shiddieq and D Indradewa. 2014. Use of Ameliorants to Increase Growth and Yield of Maize (Zea mays L.) in Peat Soils of West Kalimantan. J Trop Soils 19: 35-41. Doi: 10.5400/jts.2014.19.1.35]Â  Â Â